An Updated Review on Ethnomedicinal Uses Phytochemistry and Pharmacological Activities of Couroupita guianensis - Jagannatha, Sujatha; Maity, Subhasish; Santra, Ayantika; Kuruvalli, Gouthami; Reddy, Vaddi Damodara; Golla, Ramanjaneyulu (Pharmacognosy Reviews)
Couroupita guianensis (L), also known as cannonball tree. Couroupita guianensis (C. guianensis) belongs to the family Lecythidaceae. It is a medicinal plant that exhibited potential antibacterial and anti-cancer activity in different experimental models. Based on recent studies the plant has been shown to have many phytochemicals such as terpenoids, saponins, alkaloids, amirins, tannins etc., which exhibit strong antioxidant activity that are essential to lead a healthy life. Furthermore, the medicinal and pharmacological usefulness of plants is expanding; plant extracts have huge potential in reducing inflammatory, depressive, neuropharmacological and other illnesses. Several in vitro studies reveal that phytochemicals are helpful to treat human diseases in which free radical generation plays a significant role and which needs more in vivo research. This review elevated some potential pharmacological importance of bioactive components and their biological activity based on in vitro studies. Also, studies showed that different phytochemicals were obtained by various solvent extractions that are capable of protecting against cancer and diabetes as well as shows wound healing activities and insecticidal activities. In this review we have summarized the research work done so far on C. guianensis to treat various ailments. Also, we have emphasized the future work need to be done.
Keywords: Couroupita guianensis; Phytochemistry; Pharmacology; Medicinal uses